Teacher Candidates’ Incoming Beliefs About Teaching: Comparing Catholic Service-Learning and Traditional Programs - Khmlekov, Vladimir T.; Power, Ann Marie R.; Power, F. Clark (Catholic Education: A Journal of Inquiry and Practice, 2001)
This study analyzes a range of professional beliefs held by a sample of incoming teacher candidates in the Alliance for Catholic Education (ACE), a service-learning teacher education program at the University of Notre Dame, and a sample of preservice teachers in a traditional teacher education program at a state university. The key dependent variables in this study are preservice teachers’ sense of professional responsibility and self-efficacy beliefs regarding the intellectual and moral aspects of their teaching. Findings indicate that ACE teacher candidates hold a greater sense of responsibility for helping disadvantaged students academically and for fostering all children’s moral growth compared to their counterparts in the traditional program. This study is the first stage in a longitudinal research project that explores the effectiveness of ACE’s model of teacher education in preparing professionally competent and responsible teachers.